2018
DOI: 10.11646/zootaxa.4374.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Rare myodocopid ostracods from Mesozoic sections of Hungary: summary, revision and description of new taxa

Abstract: With the exception of polycopids, Mesozoic myodocopid ostracods are regarded as uncommon in the fossil record. They are known from a few localities in the Tethys, and most of them are considered to be pelagic forms. However, a relatively rich and taxonomically diverse material is derived from Hungarian sections; these represent various formations deposited during the Triassic to Cretaceous.The aim of this study is to summarize the current knowledge of Mesozoic myodocopids and to provide new information concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 632 publications
(7 citation statements)
references
References 0 publications
1
3
0
3
Order By: Relevance
“…This would rather indicate that Pokornyopsis did not colonize crevicular systems in the Triassic. Hungaroleberis has been reported from the Wordian, Middle Permian, of Greece (Crasquin-Soleau & Baud 1998) to the Bajocian, Middle Jurassic, of Hungary (Tóth & Cséfán 2018), and the species reported in this paper (Fig. 13G-L) correspond to its first known occurrence in the Triassic worldwide.…”
Section: Stratigraphic and Geographical Distributions: Updates And Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…This would rather indicate that Pokornyopsis did not colonize crevicular systems in the Triassic. Hungaroleberis has been reported from the Wordian, Middle Permian, of Greece (Crasquin-Soleau & Baud 1998) to the Bajocian, Middle Jurassic, of Hungary (Tóth & Cséfán 2018), and the species reported in this paper (Fig. 13G-L) correspond to its first known occurrence in the Triassic worldwide.…”
Section: Stratigraphic and Geographical Distributions: Updates And Discussionsupporting
confidence: 63%
“…The Triassic myodocopid fossil record from the North Dobrogea is rich compared to that of contemporaneous assemblages (e.g., Crasquin-Soleau & Grădinaru 1996;Sebe et al 2013;Forel & Grădinaru 2018). Until the present record, the thaumatocyprid Pokornyopsis was only known from the Jurassic (e.g., Triebel 1941;Bartenstein 1949;Aubrecht & Kozur 1995;Tóth & Cséfán 2018). Kozur (1974) and Aubrecht & Kozur (1995) mentioned the occurrence of specimens of Pokornyopsis in the late Triassic, but these were not further discussed or illustrated and Tóth & Csefan (2018) revealed that the specimens were lost.…”
Section: Stratigraphic and Geographical Distributions: Updates And Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For each time slice, localities that provided less than 3 genera are not considered as their paucity may bias the analysis, with an exception for Dienerian and Smithian that we tentatively characterize in spite of their extreme low diversity. Nekto-benthic taxa are excluded (Crasquin-Soleau and Grădinaru, 1996;Sebe et al, 2013;Forel and Grădinaru, 2018;Tóth & Cséfán, 2018). For each stage we follow the method used by Forel and Grădinaru (2018) and produced a similarity symmetric matrix, following Q-mode analysis (Supplementary File 2; e.g., Henderson and Heron, 1976;Pielou, 1979;Janson and Vegelius, 1981;Digby and Kempton, 1987).…”
Section: Patterns Of Distribution Through Timementioning
confidence: 99%
“…Célom volt még a bentosz fauna leírása mellett a medence-képződményekből előkerült ritka Myodocopa együttes leírása és értékelése is (Cséfán & Tóth 2013;Tóth & Cséfán 2018).…”
Section: Bevezetésunclassified